2013
DOI: 10.1332/204674313x665913
|View full text |Cite
|
Sign up to set email alerts
|

The making of selfhood: naming decisions on marriage

Abstract: This article outlines the ways in which British women make sense of and reconcile facets of their identities at the point of marriage through the naming decisions they make. Both name changing and name retaining are considered. The dialectic between self and others is considered, using Mead’s theories, as well the creation of gendered identity, using empirical evidence from a survey of 102 British women and 16 in-depth interviews with a smaller sample of this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…A comparative U.S./Russian study by Boxer and Gritsenko (2005) suggests that (heterosexual) women change their surnames at the naming crisis point of marriage for a variety of reasons, such as to signal family connectedness (to show marital union/commitment and family solidarity and/or to mark the beginning of a new stage of life) or as a pragmatic means of avoiding confusion over disparate surnames within a family unit (for the UK, see Thwaites 2013; Wilson 2009). These findings support arguments by scholars that surname choices are linked to family practices of the display of connectedness and affinities, of “We” identities (Almack 2005; Davies 2011; Elias 1991; Finch 2008).…”
Section: Marital and Children’s Surnamingmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparative U.S./Russian study by Boxer and Gritsenko (2005) suggests that (heterosexual) women change their surnames at the naming crisis point of marriage for a variety of reasons, such as to signal family connectedness (to show marital union/commitment and family solidarity and/or to mark the beginning of a new stage of life) or as a pragmatic means of avoiding confusion over disparate surnames within a family unit (for the UK, see Thwaites 2013; Wilson 2009). These findings support arguments by scholars that surname choices are linked to family practices of the display of connectedness and affinities, of “We” identities (Almack 2005; Davies 2011; Elias 1991; Finch 2008).…”
Section: Marital and Children’s Surnamingmentioning
confidence: 99%
“…In essence, evidence suggests that men are more likely than women are to favor the retention of conventional patronymic and patrilineal surnaming practices (in the U.S., Intons-Peterson and Crawford 1985, Scheuble and Johnson 1993a, b, Shafer 2017; in the UK, Wilson 2009). In a UK study, Thwaites (2013) found that some men became very upset if their female partner even considered the idea of not changing her surname at marriage. For me, such findings suggest a link, for some men at least, between adherence to patronymic and patrilineal surnaming practices and the validation of their masculinity.…”
Section: Marital and Children’s Surnamingmentioning
confidence: 99%
See 1 more Smart Citation
“…I det moderne samfunnet knyttes navn til egen identitet, navnet er forankret i forestillinger om selvet (Thwaites, 2013). Men navnevalget ved ekteskapsinngåelsen er omgitt av sterke sosiale normer og forventninger i USA og England.…”
Section: Etternavn: Individ Eller Familieunclassified
“…In essence, evidence suggests that men are much more likely than women to favour the retention of conventional patronymic and patrilineal surnaming practices (in the US, Intons-Peterson andCrawford, 1985 andScheuble andJohnson, 1993; in the UK, Wilson, 2009). In a UK study, Thwaites (2013) found that some men became very upset if their woman partner even considered the idea of not changing their surname at marriage. These findings suggest an association, amongst some men at least, between patronymic, patrilineal surnaming practices and the constitution and display of masculine heterosexual embodied identity.…”
Section: Naming the Sexed And Gendered Bodymentioning
confidence: 99%